Avaliação de mecanismos dosadores na distribuição longitudinal de sementes de feijão-caupi (Vigna unguiculata (L.) Walp) - Moreira, Antonio Robson (2018)
The objective was to evaluate two seed pneumatic metering mechanisms and one of a honeycomb disk in different conditions of cross slope and velocity of displacement in the longitudinal distribution of cowpea seeds. The experiment was carried out at the Research and Development Laboratory of Agricultural Machines (LASERG). Experimental design was randomized blocks with subdivided plots, containing five blocks in a factorial arrangement (3x3x3), totaling one hundred and thirty-five experimental units, in which the treatments were constituted by combinations of levels of the following factors: seed meterings (F1); cross slope (F2) with three levels, 11° degrees for left and right, besides leveled (0° degree); velocity of displacement (F3) with three levels: 1.38 meters per second (m s-1), 1.67 m s-1 and 1.94 m s-1. The variables of the responses analyzed were the percentage of acceptable, multiple and faulty spacings, besides the number of seeds per linear meter and accuracy of the acceptable spacings. After collecting data, they were submitted to statistical analysis of variance, and the significance of the factors was checked through the F-test (ANOVA, P<0.01). There was significant interaction of the metering (F1) with the cross slope (F2) on all variables analyzed and the metering with the velocity of displacement (F3) on the percentage of acceptable, multiple, faulty and number of seeds per linear meter. This last variable was also affected by triple interaction. The pneumatic disk provided higher quality in the longitudinal distribution of cowpea seeds. The honeycomb disk presented a significant reduction in the number of seeds per meter due to the variation of the cross slope and the increase in velocity. Seed metering A obtained optimal performance; B, good and C, regular.